2012
DOI: 10.1007/s13224-011-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neoadjuvant Chemotherapy (NACT) Followed by Surgical Cytoreduction in Advanced Epithelial Ovarian Cancer

Abstract: Objectives To study the role of neoadjuvant chemotherapy (NACT) followed by surgical cytoreduction in the management of advanced epithelial ovarian cancers. Methods A prospective hospital based study of patients with advanced epithelial ovarian cancers (stage III and IV) was conducted at Gujarat Cancer & Research Institute, Ahmedabad during August 2008 to August 2010. Total 50 patients were treated with NACT followed by surgical cytoreduction and followed up till August 2010. Response to NACT, optimal cytoredu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Mazzeo et al (2003) [10] Sonia et al (2010) [11] Present study (n=34 and present study, it showed that majority of patients were under Partial response 33, 27 and 31 respectively [10] . When patients with stable disease were considered Sonia et al, mazeo at al and the present study showed that there were 8 patients, 6 patients and 2 patients respectively [10,11] . When patients with progressive disease was considered mazzeo et al had 3 patients, while present study had only 1 patient.…”
Section: Responsesupporting
confidence: 49%
“…Mazzeo et al (2003) [10] Sonia et al (2010) [11] Present study (n=34 and present study, it showed that majority of patients were under Partial response 33, 27 and 31 respectively [10] . When patients with stable disease were considered Sonia et al, mazeo at al and the present study showed that there were 8 patients, 6 patients and 2 patients respectively [10,11] . When patients with progressive disease was considered mazzeo et al had 3 patients, while present study had only 1 patient.…”
Section: Responsesupporting
confidence: 49%
“…In nearly 72% cases in this study, R0 resection was achieved. This is in accordance with various studies: Deo et al 14 and Batra et al 15 (R0 ¼ 72% in each study) and one by Ghisoni et al 16 (R0 ¼ 70%). The rates of optimal debulking surgery in the EORTC trial, 8 CHORUS, 9 JCOG, 17 SCORPION, 12 and Ghisoni et al 16 were 80, 73, 82, 90, and 70%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In a study by Sonia Batra et al, optimal cytoreduction was achieved in 72% of the patients who underwent NACT followed by IDS, which was comparable to 78% complete cytoreduction rate in the present study. 10 In the EORTC trial (Table 2) by Vergote et al, the OS and PFS survival after NACT and IDS with adjuvant chemotherapy were 30 months and 12 months, respectively, and in the CHORUS trial, the values were 24.5 months and 11.7 months, respectively. 11 In study by Baruah et al, the OS and PFS after NACT followed by IDS and adjuvant chemotherapy were 26 months and 18 months, respectively, and in the present study, the OS and PFS after similar management were 21 and 20 months, respectively (Table 2).…”
Section: Discussionmentioning
confidence: 96%